Carbon-carbon windows, intended for extraction of electron-and proton beams from accelerators into atmosphere - Kovpik, O.F.; Kornilov, E.A.; Gurin, V.A.; Gurin, I.V.; Kolosenko, V.V.; Birukov, O.V.; Antipov, V.S.; Kiselev, V.A. (Вопросы атомной науки и техники, 2004)
On the basis of a carbon-carbon composite, coated with an anticorrosive coating, the authors have developed
vacuum-tight windows, made of a material, resistant to the irradiation. These windows are intended for the extraction of high-power electron- and proton beams into the atmosphere. One uses them for disinfection of large volumes
of the drinking water and its purification from toxic chemical compounds. The windows are also applied in the
branch of the electron-nuclear power engineering, where the proton beam have an energy of 1 GeV and an average
power of 30 MW must be injected into the reactor. Створені вакуумщільні вікна виводу із радіаціно-стійкого конструкційного матеріалу на основі вуглець-
вуглецевого композиту з антикорозійним покриттям для виводу в атмосферу потужних електронних і
протонних пучків. Такі вікна потрібні для прискорювача електронних пучків, при вирішенні проблеми
обеззараження і очистки води в великих об’ємах. Ці вікна можуть бути використані для елктроядерної
енергетики, вводу протонного пучка в реактор. потужністю 30 MВт. Міцністні характеристики
полусферичного вікна із вуглецевого матеріалу відповідають потребам, що пред’являються до вікна
реактора. Разработаны вакуумплотные окна вывода из радиационно-стойкого конструкционного материала на
основе углерод-углеродного композита с антикоррозийным покрытием для вывода в атмосферу мощных
электронных и протонных пучков. Такие окна необходимы для вывода из ускорителя электронных пучков,
при решении задачи обеззараживания и очистки воды в больших объемах. Эти же окна могут быть использованы для электроядерной энергетики, ввода протонного пучка в реактор мощностью 30 MВт. Прочностные характеристики полусферического окна из углеродного материала отвечают предъявляемым требованиям к окну реактора.